Investigating the Effect of Thymol Active Ingredient and ZnO Nanoparticle Conjugated by Thiosemicarbazone on the Expression of Efflux Pump and Biofilm Genes in Pseudomonas aeruginosa - Hadiseh Mokhtari; Seyedeh Tooba Shafighi; Ali Salehzadeh; Somayeh Ataei jaliseh (Journal of Genetic Resources, 2023)
Finding novel antimicrobials to treat drug-resistant Psudomonas aeruginosa is a major health challenge. In this study, ZnO nanoparticles functionalized by Thiosemicarbazone nanoparticles (ZnO@Glu-TSC NPs) were synthesized and the effect of the NPs alone and in combination with thymol on the expression of biofilm and efflux pump genes in P. aeruginosa was investigated. Physicochemical features of the ZnO@Glu-TSC NPs were evaluated by FT-IR, XRD, EDS-mapping, and SEM and TEM imaging. The inhibitory effect of ZnO@Glu-TSC NPs and thymol, alone and in combination, were determined by broth microdilution method, and quantitative PCR was used to evaluate the expression of the pelA, pslA, algD, mexA, mexB, and mexX genes. The synthesized NPs were almost spherical, without impurities, and in a size range of 20 to 60 nm. Simultaneous treatment of P. aeruginosa with ZnO@Glu-TSC and thymol had a significantly stronger inhibitory effect (MIC: 3.12-25.5 µg/mL) than either agent alone. The relative expression of the pelA, pslA, and algD genes in P. aeruginosa strains treated with ZnO@Glu-TSC+thymol was reduced by 0.44, 0.43, and 0.46 folds, respectively. Furthermore, the expression of mexA, mexB, and mexX genes decreased in P. aeruginosa strains treated with ZnO@Glu-TSC+thymol (0.42, 0.45, and 0.41 folds, respectively). Also, it was found that the combination of ZnO@Glu-TSC and thymol could synergically reduce the expression of the mentioned genes in comparison with either agent alone. This study showed that ZnO@Glu-TSC NPs and thymol synergically inhibited biofilm maturation and efflux pump systems in P. aeruginosa strains and could be considered a novel antibacterial candidate against P. aeruginosa strains.